Efikasi Beberapa Herbisida Secara Tunggal dan Campuran Terhadap Clidemia hirta (L.) D. Don. Di Perkebunan Kelapa Sawit - Abdi Hafiz; Edison Purba; B. Sengli J. Damanik (Universitas Sumatera Utara, 2014)
A field experiment was carried out in oil palm plantation to determine the efficacy of selectedherbicides to control Clidemia hirta (L.) D. Don. in oil palm plantations. Treatments were trichlopyr+ aminopylarid 333 + 17 g. ai/ha, trichlopyr + aminopylarid 416,25+21,25 g. ai/ha, trichlopyr +aminopylarid 499,5 + 25,5 g. ai/ha, trichlopyr 536 g. ai/ha, trichlopyr 536 g. ai/ha, paraquat 400 g.ai/ha + methyl metsulfuron 15 g. ai/ha, glyphosate 960 g. ai/ha + trichlopyr 251,25 g. ai/ha,glyphosate + trichlopyr 620 + 98 g. ai/ha and without treatment. The results showed that theefficacy of both single and mixed herbicides significantly affected mortality and percentage of plantdry weight 16 WAT. Herbicide trichlopyr with dose of 536 g. ai/ha was the most effective treatmentto control C. hirta (L.) D. Don. with mortality rate of 97,73%.